Planning Policies and Housing Development: Evaluating Ireland’s Fast-Track Planning Scheme 2017–2021 - Hualuoye Yang; Declan Redmond; Brendan Williams (Land)
This article examines the impact of neoliberal political–economic orientations on urban planning policies through a case study of Ireland’s Strategic Housing Development (SHD) fast-track planning scheme. By evaluating SHD applications from 2017 to 2021, this study assesses the scheme’s effectiveness in housing development in County Dublin and addresses how neoliberal policies affect planning objectives. The findings reveal that, although the SHD scheme expedited planning approvals, it faced significant challenges, including high rates of judicial review and low commencement rates for approved developments. These issues hindered the scheme’s capacity to address housing shortages effectively. The research highlights that market-driven policies often shape urban development patterns in ways that misalign with policy goals, potentially compromising social equity and long-term sustainability. By exploring the tensions between planning efficiency, industry interests, and broader policy objectives, this study contributes to ongoing debates about the role of neoliberalism in urban planning. It concludes by advocating for a more integrated approach to urban governance—one that balances economic imperatives with social and environmental priorities to promote sustainable and equitable development.